Efficacy of add-on Danhong injection in patients with unstable angina pectoris: A double-blind, randomized, placebo-controlled, multicenter clinical trial. (10th February 2022) - Chen, Lin; Fu, Guang; Hua, Qi; Zhu, Hai-Yan; Deng, Yue; Wu, Wei; Zhao, Yu-Jie; Yang, Xi-Yan; Yang, Bai-Song; Zhou, Ya-Bin; Liu, Jun; Yu, Ya-Nan; et al.
Abstract: Ethnopharmacological relevance: Danhong injection (DHI)，which is extracted from Salviae miltiorrhizae and Flos carthami ，has been widely prescribed to patients with unstable angina pectoris (UAP) in China. However, a high quality clinical trial is needed. Aim of the study: To determine whether DHI can relieve symptoms of transient myocardial ischemia in patients with unstable angina pectoris. Materials and methods: A double-blind, placebo-controlled, randomized clinical trial was conducted in nine hospitals in China. Inpatients with UAP with blood stasis syndrome (BSS) were randomized 1:1 to receive DHI or placebo. The primary outcome was improvement rate in the quantification score of angina pectoris. Secondary outcomes included blood stasis syndrome scale, nitrates use, electrocardiogram recordings, PCI procedures, Seattle Angina Questionnaire (SAQ) and biochemical indexes. Results: 160 participants were enrolled and 159 were analyzed. There was no signiﬁcant diﬀerence in primary outcome as compared with control group at the end of 7-day treatment, but significant difference at 28-day follow up (70.53% [95% CI, 59.97–81.09%] and 54.34% [95% CI, 42.68–65.99%]; P = 0.0423). The BSS score was significantly lower in the DHI group than that in the control group at day 28 (6.49 [6.96] vs 10.53 [9.07], P = 0.0034). In addition, DHI was signiﬁcantly superior to placebo in the angina stability score of SAQ (91.10 [17.37] versus 78.21 [22.08], P < 0.001). There were no significant differences in other secondary outcome measures. Conclusions: A small decrease in the total effective rate and an increase in the angina stability score were observed 28 days after implementation of DHI in UAP with a total blood stasis syndrome score decrease, but the efficacy was not observed at day 7. The findings support that DHI may potentially relieve clinical symptoms and can benefit angina stability. Clinical trial registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02007187. Graphical abstract: Image 1